Nano-coating eye drops as well as preparation method and application thereof
By forming an adhesion inner layer complexed by tannic acid and Fe3+ metal ions in the eye, and a lubricated outer layer complexed by poly2-methacryloyloxyethylphosphorylcholine with Fe3+ metal ions in the eye The nano-coated eye drops solve the problems of short residence time and low comfort of eye treatment drugs, achieve continuous release and interface lubrication, and significantly improve the treatment effect and patient comfort.
Patent Information
- Application Number
- CN202411242421.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-27
AI Technical Summary
Existing ocular therapy drugs stay on the eye surface for a short time, resulting in frequent administration, increasing ocular surface toxicity and reducing patient compliance, and nonselective adhesion may lead to obstruction of eyelid movement and blurred vision.
Nano of the lubricated outer layer formed by the coordination complex of tanninic acid and Fe3+ metal ions and the coordination complex of poly2-methacryloyloxyethylphosphorylcholine and Fe3+ metal ions Coated eye drops form a double-layer nanocoated structure that provides continuous drug release and interface lubrication to avoid adhesions.
It realizes long-term stay and continuous release of drugs on the eye surface, reduces the number of blinks, improves the treatment effect and comfort, significantly reduces corneal opacity and neovascularization, and promotes wound healing.
Smart Images

Figure CN119185190A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, and in particular to a nano-coated eye drop, a preparation method and application thereof. Background Art
[0002] Ocular drug delivery is the most common method for treating eye diseases. Eye drops and eye ointments are the main ways of topical drug delivery on the ocular surface, which is a non-invasive and easy-to-use treatment method. However, there are innate protective mechanisms in the eye, such as corneal barriers, blinking activities, and tear circulation, which seriously hinder the penetration of the administered drugs. These factors inevitably lead to short drug residence time and increased frequency of administration. For example, in the treatment of keratitis, more than 6 times a day of corticosteroids are required. However, frequent administration may cause ocular surface toxicity and reduce patient compliance. To meet this challenge, various drug delivery systems have been studied for sustained release of drugs on the ocular surface. For example, surface roughness-controlled ceria nanocages and poly-l-histidine surface coatings were prepared to prolong the release of drugs on the ocular surface. To further prolong the residence time of drugs on the ocular surface, a coating based on o-nitrobenzaldehyde-modified gelatin was reported to be covalently bound to the corneal surface. Although adhesive forms of ophthalmic drugs are expected to prolong release, nonselective adhesion to the cornea and eyelids often hinders eyelid movement, and deposition, spatter, and crusting around the eyelids often cause discomfort and blurred vision. In severe cases, these problems can induce superficial corneal opacities.
[0003] Therefore, in order to treat eye diseases, there is an urgent need to develop a non-invasive ocular drug delivery system with a long ocular surface residence time and high comfort. Summary of the invention
[0004] The purpose of the present invention is to overcome the defect that the existing eye treatment drugs have poor treatment effects.
[0005] In order to achieve the above object, the present invention provides a method for preparing nano-coating eye drops, which comprises at least the following steps:
[0006] Step 1: Mix tannic acid solution with Fe 3+ The metal ion solution is mixed evenly, and the catechol group of the tannic acid is mixed with the Fe 3+ The metal ions are coordinated and complexed, and after the first step of dripping, an adhesion inner layer is formed; the drug dexamethasone is dripped into the adhesion inner layer, and the mixture is blown and mixed to obtain the adhesion inner layer loaded with the drug;
[0007] Step 2, dripping the poly 2-methacryloyloxyethyl phosphorylcholine solution in the second step, the phosphorylcholine groups in the poly 2-methacryloyloxyethyl phosphorylcholine solution are attached to the Fe 3+ The metal ions undergo coordination and complexation to form a lubricating outer layer;
[0008] The drug-loaded adhesive inner layer and the lubricating outer layer constitute nano-coating eye drops.
[0009] Preferably, in molar ratio, the tannic acid solution: Fe 3+ Metal ion solution = 1:3.
[0010] Preferably, the surface pores of the adhesive inner layer are larger than the surface pores of the lubricating outer layer.
[0011] Preferably, the depth of the surface pores of the adhesive inner layer is greater than the depth of the surface pores of the lubricating outer layer.
[0012] Preferably, in the adhesive inner layer loaded with drugs, the concentration of the drugs is 1 mg / mL.
[0013] The present invention also provides a nano-coating eye drops, which are prepared by the above-mentioned preparation method.
[0014] Preferably, the nano-coated eye drops comprise an adhesive inner layer and a lubricating outer layer, wherein the adhesive inner layer is composed of tannic acid and Fe 3+ The lubricating outer layer is formed by the coordination complexation of metal ions, and the phosphorylcholine groups in the poly (2-methylpropylene glycol) phosphorylcholine solution and Fe 3+ Coordination complex formation of metal ions.
[0015] The present invention also provides an application of nano-coating eye drops, wherein the nano-coating eye drops are used for preparing a medicine for treating corneal contusion.
[0016] Preferably, the nano-coating eye drops are used to prepare medicines for treating corneal alkali burns.
[0017] Compared with the prior art, the beneficial effects of the present invention include at least:
[0018] (1) After continuous topical administration of the nano-coated eye drops in the form of eye drops, a double-layer nano-coating structure including an adhesive inner layer and a lubricating outer layer is formed, wherein the adhesive inner layer is composed of tannic acid and Fe 3+ The metal ion coordination complex is formed, and the adhesive inner layer can be retained on the eye surface for a long time to provide sustained release of drugs; the lubricating outer layer is composed of the phosphorylcholine group in the poly 2-methacryloyloxyethyl phosphorylcholine solution and Fe 3+ The metal ion coordination complex and lubricating outer layer provide interfacial lubrication to ensure comfort and prevent adhesion between the nano-coating and the eyelid.
[0019] (2) The nano-coated eye drops of the present invention exhibit a long ocular surface residence time both in vitro and in vivo. Once-daily instillation can allow the administered drug to reach a sufficient local concentration in the eye, thereby enhancing the therapeutic effect, and can also significantly reduce the number of blinks, providing better comfort.
[0020] (3) The nano-coating eye drops of the present invention can treat corneal contusion and corneal alkali burn, and can significantly reduce corneal opacity, reduce the degree of neovascularization, and improve the wound healing rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The schematic diagram of the design and preparation of a nano-coating eye drop (adhesive lubricative Janusnanocoating, ALJN) of the present invention is as follows:
[0022] (A) Design and preparation route of ALJN; (B) ALJN eye drops prolonged precorneal retention, sustained drug release, and improved ocular comfort after ocular administration; (C) Tannic acid / dexamethasone-mediated dual anti-inflammatory effects of ALJN eye drops in promoting corneal injury healing.
[0023] Figure 2 Characterization of the nano-coated eye drops ALJN of the present invention:
[0024] (A) Transmission electron microscopy (TEM) images of the inner layer (SL) and double layer (DL) surfaces. Scale bar: 200 nm; (B) Scanning electron microscopy (SEM) images of the SL and DL surfaces. Scale bar: 500 nm; (C) Atomic force microscopy (AFM) images of the cornea, SL, and DL surfaces. Scale bar: 500 nm; (D) Average roughness of the cornea, upper, and lower three-layer surfaces; (E) SEM image of the cross section of SL and DL on agar slices. The dotted white box indicates the coating. Scale bar: 200 nm; (F) The coating thickness of SL and DL on agar slices; (G) SEM image of the cross section of SL and DL on the corneal surface. The dotted white box indicates the coating. Scale bar: 200 nm; (H) The coating thickness of SL and DL on the corneal surface; (I) Fe 3+ and Fe 3+ UV spectrum of the mixture with poly (2-methacryloyloxyethyl) phosphorylcholine (PMPC); (J) Mass spectrometry analysis of drug-loaded nanocoatings; (K) Fe 3+ (L) The effect of the molar ratio of dexamethasone (DEX) to tannic acid (TA) on the drug loading efficiency of the nanocoating; (M) The effect of the dexamethasone (DEX) dosage on the drug loading efficiency of the nanocoating.
[0025] Figure 3The in vitro functions of the nano-coated eye drops ALJN of the present invention are as follows:
[0026] (A) Fluorescence images of the nanocoating at specific time points in vitro; (B) Relative average fluorescence intensity of the nanocoating at specific time points in vitro; (C) SL and DL contact angle imaging; (D) SL and DL contact angles; (E) Schematic diagram of the in vitro sliding distance determination of agar slices; (F) The sliding distance of agar on glass after infiltration with different concentrations of PMPC; (G) The sliding distance of agar on glass after infiltration with SL and DL; (H) The inhibitory effect of different coating components on the production of NO by inflammatory cells induced by lipopolysaccharide (LPS); (I) The cumulative release amount of DEX in the nanocoating; (J) The effect of different coating components on cell activity.
[0027] Figure 4 This is the in vivo functional verification of the nano-coated eye drops ALJN of the present invention:
[0028] (A) Confocal images of nanocoatings on the mouse corneal epithelium at specific time points after eye drops. Blue is the nucleus stained with DAPI, and green is the nanocoating labeled with FITC. Scale bar: 50 μm; (B) Schematic diagram of the in vivo experiment of the retention time of nanocoatings on the mouse ocular surface; (C) The number of mouse eyes with green fluorescence observed in the presence of nanocoatings at each time point; (D) The number of mouse blinks within 5 minutes after topical administration; (E) Slit lamp microscope images of mice after eye drops were applied once a day for 5 consecutive days, arranged from left to right as upright, lateral, and images under cobalt blue filter after sodium fluorescein staining; (F) Immunofluorescence staining images of damaged corneal sections. Left column, corneal contusion. Right column, alkali-burned cornea. Blue represents nuclei and green represents TNF-α. Scale bar: 50 μm; (G) Relative concentration of tumor necrosis factor-α (TNF-α) in the cornea of mice with corneal contusion; (H) Relative concentration of interleukin-1β (IL-1β) in the cornea of mice with corneal contusion; (I) Relative concentration of TNF-α in the cornea of mice with corneal alkali burn; (J) Relative concentration of interleukin-6 (IL-6) in the cornea of mice with corneal alkali burn.
[0029] Figure 5 The therapeutic effect of the nano-coated eye drops ALJN of the present invention on the mouse corneal contusion model:
[0030] (A) Flow chart for evaluating the therapeutic effect of nanocoating on corneal contusion mouse model. After modeling, eye drops were applied once a day for 3 consecutive days; (B) Upright image of mouse eyes under white light; (C) Side image of mouse eyes under white light; (D) Image of mouse eyes under cobalt blue filter after sodium fluorescein staining; (E) Corneal opacity score of mice in each group; (F) Corneal neovascularization area of mice in each group; (G) Corneal wound healing area ratio of mice in each group; (H) Corneal sections, top layer is H&E staining, middle layer is Masson staining, and bottom layer is immunohistochemical staining (MPO). Scale bar: 100μm; (I) Relative corneal thickness of mice in each group; (J) Relative cell count in mouse cornea.
[0031] Figure 6 The therapeutic effect of the nano-coated eye drops ALJN of the present invention on the mouse corneal alkali burn model:
[0032] (A) Flow chart for evaluating the therapeutic effect of nano-coating on corneal alkali burn mouse model. After modeling, eye drops were applied once a day for 5 consecutive days; (B) Upright image of mouse eyes under white light; (C) Side image of mouse eyes under white light; (D) Image of mouse eyes under cobalt blue filter after sodium fluorescein staining; (E) Corneal opacity score of mice in each group; (F) Corneal neovascularization area of mice in each group; (G) Corneal wound healing area ratio of mice in each group; (H) Corneal sections, top layer is H&E staining, middle layer is Masson staining, and bottom layer is immunohistochemical staining (MPO). Scale bar: 100μm; (I) Relative thickness of mouse cornea after treatment; (J) Relative cell count in mouse cornea.
[0033] Figure 7 The synthesis verification of PMPC of the present invention is as follows: hydrogen nuclear magnetic resonance spectra of MPC and PMPC.
[0034] Figure 8 Verification of the PMPC synthesis of the present invention: infrared spectra of MPC and PMPC.
[0035] Fig. 9 It is the gel permeation chromatography curve of PMPC of the present invention.
[0036] Fig.10 The coating thickness measurement of the present invention: the coating thickness of SL and DL was measured using a step profiler.
[0037] Fig.11 The proof of the present invention on the coating equipped with DEX: infrared spectra of SL, DEX and SL+DEX.
[0038] Fig.12 The present invention explores the conditions for coating with DEX:
[0039] (A) The effect of the interval time before PMPC addition on the drug loading efficiency of the nanocoating; (B) The effect of different DEX dosages on the actual drug loading of the nanocoating.
[0040] Fig.13 Detection of the macroscopic lubrication properties of SL and DL of the present invention on the agar surface: Representative pictures of agar sliding on glass after being infiltrated with SL and DL, respectively.
[0041] Fig.14 Detection of the long-term retention function of the coating of the present invention on the ocular surface: Confocal image of the nanocoating formed on the mouse corneal epithelium at a specified time point after administration. Blue represents the cell nucleus, and green fluorescence represents the nanocoating labeled with FITC (Fluorescein Isothiocyanate). Scale bar: 50μm. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The experimental materials not specifically mentioned in the present invention are all conventional commercially available materials, and the experimental methods not specifically mentioned in the present invention are all conventional experimental methods.
[0043] In recent years, the "Janus" structure has attracted widespread attention due to the opposite properties of its two sides. Specifically, this structure can firmly adhere to the surface of damaged tissue on the one hand, and has a lubricating effect on the other hand, effectively preventing adhesion between tissues. In recent years, it has been widely used in tissue repair, for example, for gastric perforation repair, heart repair, abdominal wall repair, and tendon repair. Therefore, constructing an ocular surface nanocoating with a "Janus" structure is expected to achieve long-lasting ocular surface adhesion and good lubricity to avoid eyelid adhesion after drug administration, thereby simultaneously extending drug residence time and improving patient comfort.
[0044] like Figure 1 As shown, the present invention provides an asymmetric nano-coating eye drops, which is composed of an adhesive inner layer loaded with drugs and a lubricating outer layer. The adhesive inner layer is composed of tannic acid (TA) and Fe 3+ The outer layer is formed by the coordination complex of metal ions, and the phosphate group of poly (2-methacryloyloxyethyl) phosphorylcholine (PMPC) and Fe 3+The coordination complex of metal ions is formed. Due to the adhesion, the polyphenol inner layer is able to bind to the ocular surface and provide a reservoir for drug loading and sustained release. At the same time, considering the antifouling properties of the polymer, the zwitterionic (PMPC) outer layer can avoid poor eyelid adhesion and obtain good comfort. In in vivo studies, the present invention found that after continuous instillation, the retention time of the obtained adhesive lubricating nanocoating (ALJN) on the mouse ocular surface was greatly improved and could be extended to 24 hours. More importantly, ALJN was able to reduce the blinking frequency from 12 times / minute to 3 times / minute, verifying its high comfort.
[0045] In addition, the anti-inflammatory eye drug dexamethasone (DEX) was selected as a model drug and loaded into the inner layer of ALJN for the treatment of corneal damage. Due to the natural anti-inflammatory effect of TA and the continuous release of DEX during retention on the ocular surface, ALJN showed its therapeutic value for corneal damage in two mouse models of corneal contusion and corneal alkali burn. In the case of once-daily administration, ALJN showed superior anti-inflammatory therapeutic effects, which was reflected in the improvement of corneal transparency and the significant reduction of damaged areas and neovascularization areas. The nano-coated eye drops provided by the present invention can be sequentially instilled on the surface of the eye to form a TA-Fe 3+ The asymmetric nanocoating composed of an inner layer and a PMPC outer layer has a simple preparation process. 3+ The inner layer not only provides a reservoir for drug encapsulation and release, but also has natural polyphenol anti-inflammatory function. The in situ formation of a nano-coated eye drop of the present invention can provide a multifunctional platform for the development of local drug delivery systems for the treatment of eye diseases.
[0046] Experimental Materials
[0047] The chemicals used in this study include TA (Aladdin, Shanghai, China), ferric chloride hexahydrate (Fe 3+ ) (BBI, Shanghai, China), dexamethasone (CAS: 50-02-2, LABLEAD, Beijing, China), 2-methylpropanediol phosphocholine (MPC) (Bidepharm, Shanghai, China), azobisisobutyronitrile (AIBN) (Rhawn, Shanghai, China), FITC (Aladdin) and NaOH (BBI). The water used in the experiment was purified by Millipore milliq purification system.
[0048] Experimental animals
[0049] Male C57BL / 6J mice (6–8 weeks old) were purchased from Spectro (Beijing) Biotechnology Co., Ltd. Mice were randomly divided into groups. Mice were housed in a specific pathogen-free environment under controlled conditions with a 12-h light / dark cycle at 20–22°C. All animal experiments were performed in accordance with the guidelines of the Institutional Animal Care Ethics Committee and the Laboratory Animal Ethics Committee of the Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine (SH9H-2023-A85-1).
[0050] Preparation and characterization of PMPC
[0051] The MPC monomer and AIBN initiator were combined in a reaction flask and vacuum dried to remove moisture. Next, the mixture was dissolved in methanol. In order to eliminate oxygen in the system, the reaction mixture was purged with nitrogen for 30 minutes. Subsequently, the flask was heated to 60°C in a water bath and reacted for 10 hours. After the reaction was completed, the mixture was cooled in an ice bath. The reaction mixture was then precipitated in a large amount of ice-cold ether to obtain a white gel-like precipitate. The precipitate was collected by centrifugation and washed three times to remove impurities. The final product, PMPC, was obtained by freeze drying. PMPC was synthesized by free radical polymerization and characterized by hydrogen nuclear magnetic resonance spectroscopy ( 1 (H NMR) Figure 7 ) and Fourier transform infrared (FTIR) spectroscopy ( Figure 8 ) confirmed the successful synthesis of PMPC. Gel permeation chromatography (GPC) showed that its weight average molecular weight was 690 kDa ( Fig. 9 ).
[0052] Preparation and characterization of ALJN
[0053] The transparent TA solution was mixed with the light yellow Fe 3+ The metal ion solutions are mixed in proportion. 3+ The coordination complex between metal ions produces a blue-purple liquid. After the first step of dripping, an adhesive inner layer (SL) is formed. PMPC contains abundant phosphorylcholine groups, which can bind to the Fe 3+ The metal ions undergo complexation and form a double layer (DL) after the second injection. Figure 2 A) and scanning electron microscopy (SEM) ( Figure 2 B) Observe the surface morphology of SL and DL. The details are as follows:
[0054] 1PMPC was measured by H NMR spectrometer (Bruker Avance Neo 400M, Billerica, Massachusetts, USA) using deuterated water as solvent and ultrasonic treatment for 5 min.
[0055] The surface morphology of SL and DL was photographed using a scanning electron microscope (Hitachi, Regulus 8230, Tokyo, Japan) and a transmission electron microscope (Hitachi, HT7700). The silicon wafer was soaked in piranha solution for 10 minutes, ultrasonically cleaned with deionized water for 10 minutes, rinsed with ethanol, and blown dry with nitrogen. SL and DL were dropped on a clean silicon wafer, and then imaged by scanning electron microscopy after drying. SL and DL were applied to a 400-mesh carbon grid and allowed to stand for 10 minutes. Excess liquid was absorbed with filter paper, the grid was air-dried, and then TEM imaging was performed.
[0056] The surface roughness of the nanocoating was measured using an AFM (Bruker NanoWizard, Billerica, Massachusetts, USA). The cornea and nanocoating were imaged using a SCANASYST-AIR probe. All imaging experiments were performed in a vibration isolation box at room temperature. For each sample, the "PeakForce quantitative imaging" operating mode was used to generate an indentation force curve with a force set point of 5 nN.
[0057] The thickness of the nanocoating was measured using a scanning electron microscope and a step profiler (KLA, Alpha-step D-600, Milpitas, California, USA). SL and DL were dripped into the agar slice and cornea, respectively. After freeze-drying, the sample was fractured in liquid nitrogen and then observed in cross section under a scanning electron microscope. The silicon wafer prepared according to the above steps was dripped with SL and DL solutions for 1 minute, respectively. Gently rinsed twice with deionized water, air-dried, and the thickness was quantified using a step profiler.
[0058] The Fe 3+ The interaction between Fe 3+ The (0.8 mg / ml) solution alone or mixed with an equal volume of PMPC (1 mg / ml) solution was vortexed for 30 s and the spectrum was scanned using a spectrophotometer.
[0059] The samples were analyzed using a mass spectrometer (Thermo ISQ EM, Waltham, Massachusetts, USA) and a FTIR spectrometer (Thermo Scientific TM NicoletTM iS50, Waltham, Massachusetts, USA) was used to characterize the presence of DEX in the nanocoating. A 0.3% (w / v) agar gel was prepared. A volume of 200 μl of Fe 3+ (0.8mg / ml) solution was added to a 48-well plate coated with agar gel, vortexed for 1min, then 200μl of TA (5mg / ml) solution was added, vortexed for 1min, and then 100μl of DEX (10mg / ml) was added, vortexed for 5min, the supernatant was discarded, and the gel was washed twice with deionized water. The gel was extracted with a spatula soaked in the solution, and a slice of about 5mm containing the surface coating was cut out and placed in 2ml of deionized water and vortexed for 30 minutes to dissolve. The sample was then filtered with a 0.22μm filter membrane and analyzed by mass spectrometry. 1% (w / v) agar gel was used as a substrate in a 48-well plate. An equal amount of Fe 3+ (0.8mg / ml) and TA (5mg / ml) were added to the agar surface in sequence and incubated for 1min. Subsequently, DEX (10mg / ml) solution was added and incubated for 5min. After that, PMPC (1mg / ml) solution was added and incubated for 1min, then the entire solution was aspirated and the gel was rinsed twice. A 5mm gel slice containing the nanocoating was cut and incubated in water for 4 hours to soften the agar gel. The drug-loaded agar gel was freeze-dried together with the solution. The resulting solid was then characterized by FTIR.
[0060] The surface wettability of the nanocoatings was characterized using a contact angle tester (kruss, Hamburg, Germany). The silicon wafers were immersed in the SL and DL solutions for 1 min, and then the excess liquid was removed with filter paper. After air drying for 5 min, the static contact angle of the nanocoatings was measured using the sessile drop method.
[0061] The DEX loading and release curve were detected by high performance liquid chromatography (HPLC, Agilent 1260 InfinityII) using the previously established DEX standard curve. 1% agar was used to simulate the ocular surface environment, and Fe 3+(0.8mg / ml) and TA (5mg / ml) were mixed with DEX to form the SL layer. After mixing, the supernatant was discarded and PMPC (1mg / ml) was added to form the DL structure. After the nanocoating was stabilized, the supernatant was taken and the unencapsulated DEX was quantified in three samples by HPLC. On this basis, the encapsulation efficiency of DEX was calculated. Similarly, after the nanocoating was stabilized, the supernatant was replaced with PBS and continuously shaken on a vortexer. At different time points (5, 10, 15, 30, 45min, 1, 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 24h), equal amounts of supernatant were taken and the release concentration of DEX at each time point was quantitatively determined by HPLC, and the percentage of drug release was calculated. The HPLC conditions were: a diamonsil C18 column (5μm, 150×4.6mm) was used; the mobile phase was a mixture of acetonitrile and water in a ratio of 30:70. The column temperature was maintained at 37°C, the absorbance wavelength was 240 nm, the injection volume was 5 μl, and the flow rate was 1.0 ml / min.
[0062] The results showed that the pores on the SL surface were larger and deeper, while the pores on the DL surface were smaller and shallower, resulting in a rougher SL surface and a smoother DL surface. The corneal surface imaged by atomic force microscopy (AFM) and the corneal surface after coating showed that the average roughness of the DL surface was similar to that of the bare corneal surface, but significantly lower than that of the SL surface ( Figure 2 To measure the layer thickness, SL and DL were first deposited on the surface of the silicon wafer and analyzed by a step profiler ( Fig.10 ). The average thickness of SL and DL were 90.90±36.28nm and 151.56±57.54nm, respectively. To further measure the thickness on a more hydrophilic surface, SL and DL were formed by dripping on the surface of an agar sheet simulating the cornea ( Figure 2 The cross-section of the freeze-dried nanocoating was observed by scanning electron microscopy. The results showed that the thickness of SL and DL were 201.95±26.71nm and 310.50±30.04nm, respectively. Figure 2 F). Similar results were found by using mouse cornea samples, similar to the agar surface simulating the cornea ( Figure 2 G,H). The ideal thickness of ophthalmic formulations should be kept below 1000nm. Therefore, the thickness of this nanocoating can be considered moderate and will not cause additional problems due to excessive thickness. 3+ Compared with the UV spectra of metal ion solutions, Fe 3+ The mixture of metal ions and PMPC showed a blue shift in the absorption peak ( Figure 2This indicates that there is an interaction between the two components (i.e., hypochromic effect and blue shift of absorption peak), thus forming a stable double-layer structure.
[0063] Next, the drug loading of the nanocoating was examined. DEX is a classic corticosteroid drug that was loaded by adding DEX solution during the complexation process to form SL. Mass spectrometry confirmed that the drug was successfully loaded into the nanocoating, with the presence of a molecular peak [M+H] at a mass-to-charge ratio (M / z) of 393.24. + ( Figure 2 J). The FTIR spectra of SL, DEX and SL+DEX also confirmed the encapsulation of DEX in the nanocoating ( Fig.11 In the spectrum of the drug-loaded nanocoating, stretching vibrations of the carbonyl bond (-C=O) in DEX were observed at 1665 and 1604 cm-1. Interestingly, in Fe 3+ Under different concentrations and feed ratios of metal ions and TA, the loading efficiency of DEX calculated by HPLC always remained at around 50% ( Figure 2 Therefore, the present invention selects 0.8mg / ml Fe 3+ Metal ions and 5 mg / ml TA were used as preparation conditions for subsequent experiments. Then, the present invention studied the effect of changing the interval between SL formation and PMPC solution addition on DEX loading efficiency. Fig.12 As shown in A, as the interval time increases from 30s to 120s, its attenuation trend gradually decreases. The loading efficiencies at 30, 60, and 120s were 53.58±0.59%, 45.42±2.12%, and 41.40±60.63%, respectively. Therefore, a 30s interval was selected to add the PMPC solution to prepare the nanocoating. In addition, the effect of different DEX addition amounts on the loading content was also studied ( Figure 2 As expected, the drug loading increased significantly as the amount of DEX added increased from 10 μg to 90 μg ( Fig.12 B). It is worth noting that within this dosage range, the loading efficiency of DEX can be maintained above 45%. Considering that the concentration of DEX free-dose to the ocular surface in in vivo studies is usually 1 mg / ml, the final amount of DEX added to the nanocoating was determined based on this, that is, 20 μg DEX was added to 20 μl ALJN for each administration.
[0064] Lubricating, retaining and anti-inflammatory properties of ALJN in vitro
[0065] The biocompatibility of the coating was evaluated in epithelial cells using the CCK-8 method (Beyotime, Shanghai, China). Cells were seeded in 96-well plates at a density of 10,000 cells per well and exposed to different components of the nanocoating, with 6 replicates per group. Incubate for 24 h at 37 ° C, 90% humidity, and 5% CO2. After incubation, the supernatant was taken and the cells were washed twice with 100 μl PBS. Then, 100 μl of culture medium containing 10 μl CCK-8 solution was added to each well, and the plate was returned to the incubator for 1 hour under the above conditions. The optical density at 450 nm was measured using a multifunctional microplate tester (BioTek, Vermont, USA), and cell viability was calculated based on this.
[0066] The in vitro anti-inflammatory function of the nanocoating was determined using a nitric oxide assay kit (Beyotime). J774A1 cells, a mouse macrophage cell line commonly used to study inflammatory responses, were seeded in 96-well plates at a density of 10,000 cells per well. The cells were then co-incubated with the different components of the nanocoating, with each group repeated 3 times. Then, 100 μl of full culture medium containing 100 μg / ml LPS (Beyotime, China) was added to each well to stimulate the cells. The cells were then incubated for 24 hours under the above conditions. After incubation, a nitric oxide (NO) detection reagent was used. 50 μl of Griess reagent I was added to each well, followed by 50 μl of Griess reagent II. After allowing the reaction to proceed for a period of time, the optical density at 450 nm was measured using a multifunctional microplate tester. The measured absorbance was then compared with the previously examined NO standard curve to calculate the concentration of NO produced in each sample.
[0067] Add Fe on the surface of 1% agar 3+ Metal ions (0.8 mg / ml) and TA (5 mg / ml) were mixed with sodium fluorescein (0.1%) (Adamas, Shanghai, China). After thorough mixing, the supernatant was discarded and PMPC (1 mg / ml) was added to form the DL structure. In the control group, all components except sodium fluorescein were replaced with PBS. Once the coating was stable, the supernatant was discarded and PBS was added. The coated agar surfaces of different groups were shaken on a vortexer for different time periods (0, 1, 2, 4, 8 and 24 h). The coatings were illuminated using cobalt blue light, and photos of the nanocoatings were taken to measure the average fluorescence intensity of the green fluorescence. This intensity was compared with the intensity at the 0 h time point, and the proportion of the remaining fluorescence was calculated.
[0068] The results showed that after the simulated cornea agar slice was immersed in the SL solution, it was observed that the agar slice did not slide, which indicated that TA-Fe 3+The surface adhesion ability of the inner layer. In order to observe its retention performance, sodium fluorescein, a fluorescent indicator commonly used in ophthalmic examinations with a molecular weight close to DEX, was placed in the nanocoating. The retention of the nanocoating was expressed by the ratio of the mean fluorescence intensity (MFI) after incubation for different times in a physiological environment of phosphate buffered saline (PBS) with gentle shaking. The control group used a sodium fluorescein solution of the same concentration ( Figure 3 A, B). It is noteworthy that at 0 h, the fluorescence intensity of the control group was higher than that of the nanocoating group due to the free form. After 0.5 h, the nanocoating group retained 93.97 ± 0.43% of the mean fluorescence intensity (MFI), while the control group only retained 22.41 ± 3.24%. After 4 h of incubation, the nanocoating group maintained 90.01 ± 0.34% of the MFI. Unfortunately, the fluorescence of the control group almost completely disappeared (0.65 ± 0.78%). Even after 24 h, the nanocoating group was still able to retain 49.41 ± 7.80% of the MFI, showing its persistent adhesion ability for more than 24 h in vitro.
[0069] In order to evaluate the interfacial lubrication effect of the PMPC layer, the contact angles of SL and DL were measured. Figure 3 C and Figure 3 As shown in D, the contact angles of SL and DL were 21.68 ± 1.64° and 30.45 ± 2.90°, respectively. The increase in contact angle indicates that DL has a higher surface tension than SL, which may lead to reduced wettability and enhanced lubricity. To quantitatively analyze the lubricity of PMPC, the distance that the agar piece slid on the glass after being immersed in PMPC solutions of different concentrations was measured ( Figure 3 E). When the PMPC concentration was 0.5 and 1 mg / ml, the sliding distances were 4.76 ± 1.01 and 5.14 ± 0.58 cm, respectively, showing a significant interfacial lubrication effect. However, as the PMPC concentration increased further, the sliding distance decreased significantly. Figure 3 As shown in the F, at 5 and 10 mg / ml, they dropped to 2.32 ± 0.99 and 0.16 ± 0.19 cm, respectively. Therefore, in subsequent experiments, PMPC with a concentration of 1 mg / ml was selected to prepare the nanocoating. Fig.13 As shown, the lubricity of the agar sheet with DL surface is greatly improved compared with that of the agar sheet with SL surface. The lubricity of the PMPC layer was further measured by calculating the sliding distance of the coated agar sheet. It is worth noting that the sliding distance of the DL surface is 4.33 ± 2.53 cm, which is 5.78 times that of the SL surface, confirming the lubricity of the nanocoating ( Figure 3 G).
[0070] The present invention also evaluated the anti-inflammatory effect of ALJN in vitro. Macrophages activated by lipopolysaccharide (LPS) initiate inflammatory pathways, and the production of nitric oxide (NO) after co-incubation with different components of the nanocoating reflects the inflammatory level of macrophages ( Figure 3 The results showed that, similar to free DEX and DEX-loaded DL, the NO level after co-incubation with SL or DL was not significantly different from that of the blank group, indicating that TA has the inherent property of inhibiting inflammation. After loading with DEX, the nanocoating can exert a dual anti-inflammatory effect. In order to achieve sustained drug delivery, the sustained release of the nanocoating is crucial. The kinetics of slow oscillatory release of DEX in PBS were studied. Figure 3 As shown in Figure 1, the release of DEX from the nanocoating occurs in two stages: initially, about 30% of the loaded DEX is released rapidly within the first hour, followed by a continuous slow release over time. After an interval of 24 h, about 45% of DEX is released, indicating that the drug-loaded nanocoating is capable of long-term continuous release of the drug. For ocular surface applications, the biocompatibility of the formed coating is essential. Therefore, the components of the nanocoating were tested for cell biocompatibility ( Figure 3 J). The results of CCK-8 assays showed that co-incubation with SL, PMPC or DL for 24 h had limited adverse effects on the proliferation of human corneal epithelial cells, indicating that the nanocoating had low cytotoxicity.
[0071] ALJN's continued retention, lubrication and anti-inflammatory properties in the body
[0072] Synthesis of TA-FITC: TA was stirred with 25-28% NH3·H2O for 1 h and dried at 80°C. The product was added to a 0.1M Na2CO3 buffer solution at pH 9.0, and a dimethyl sulfoxide (DMSO) solution of FITC was introduced. The reaction was carried out overnight, and then the product was dialyzed to obtain a TA-FITC solution. A FITC suspension was prepared in the control group, and the fluorescence intensity of FITC at different concentrations was measured using a fluorescence spectrophotometer (Horiba, Kyoto, Japan). The FITC concentration with the same fluorescence intensity as the 5mg / ml TA-FITC suspension was detected to be 4.3μg / ml.
[0073] Male C57BL / 6J mice (6-8 weeks old). Prepare 0.8 mg / ml Fe 3+An equal volume mixture of 50 μg / ml TA-FITC and 5 mg / ml TA-FITC was administered to the mouse ocular surface, 20 μl of each. The eye drops were observed for 30 seconds after administration, and the mice were not prevented from blinking thereafter. The control group was replaced with FITC in PBS. The mice were euthanized at different time points of 0.5, 2, 4, 8, and 24 h after administration. The eyeballs were fixed with eyeball fixative (Servicebio, Wuhan, China) and then embedded in Tissue-Tek OCT (SakaruFinetek, Tokyo, Japan) for frozen sections. The cell nuclei were stained with DAPI (Beyotime), a fluorescent dye that binds to DNA. Corneal images were captured using a laser scanning confocal microscope (LSCM) (Leica, Nussloch, Germany).
[0074] The results show that: in order to confirm the long-term retention of the nanocoating on the surface of the eye, the present invention uses fluorescein as an indicator. In order to prevent free fluorescein from being taken up by cells, the present invention couples fluorescein isothiocyanate (FITC) with TA to form TA-FITC, and uses it as a component to form the nanocoating. After the nanocoating was dripped into the mouse ocular surface in the form of eye drops, the mice were euthanized at 0.5, 2, 4, 8 and 24 hours. Their eyes were frozen and sectioned to observe the presence of fluorescence on the corneal surface to check whether the nanocoating was retained on the surface of the eye. The control group was given a FITC solution of the same fluorescence intensity. With the help of confocal imaging, a thin layer of green fluorescence can be observed adhering to the blue corneal tissue ( Figure 4 A, B and Fig.14 ). By counting the number of mouse eyes that maintain FITC fluorescence, the presence of FITC fluorescence on the ocular surface is quantitatively reflected ( Figure 4 C). The results showed that only one mouse in the control group retained fluorescence on the ocular surface at 0.5h and 2h, respectively. In contrast, fluorescence was observed in all six mice in the nanocoating group at 0.5, 2, and 4h. Even 24h after injection, fluorescence was observed on the ocular surface of two mice, indicating that the nanocoating can stay on the mouse ocular surface for up to 24h.
[0075] In order to evaluate the lubricating effect of the nanocoating in vivo, the present invention calculated the number of blinks of mice within 5 minutes after the nanocoating was instilled on the ocular surface as an indicator of the comfort of the eye drops ( Figure 4D). Compared with the control group, after SL was injected into the ocular surface, the average number of blinks of mice within 5 minutes increased significantly, which was 60.50±12.29 times. In contrast, after DL was injected into the ocular surface, the average number of blinks of mice within 5 minutes was only 16.50±10.75 times, which was not significantly different from the control group, verifying the satisfactory comfort of the nanocoating. In order to evaluate the in vivo compatibility of the nanocoating, the morphology of the mouse ocular surface was observed in the frontal and lateral positions using a slit lamp after daily instillation for 5 consecutive days. After sodium fluorescein injection, the ocular surface was observed under cobalt blue light. It is worth noting that after continuous administration, no abnormalities such as morphological changes, corneal opacity, corneal neovascularization, and corneal damage were observed on the mouse ocular surface ( Figure 4 E), indicating that the nanocoating has good ocular surface biocompatibility.
[0076] In order to determine the in vivo anti-inflammatory effect of the drug-loaded nanocoating, the present invention established a mouse corneal alkali burn and corneal contusion model. Corneal alkali burns were treated with eye drops for 5 days and corneal contusions were treated for 3 days. After the treatment period, the mice were euthanized, and paraffin sections and immunofluorescence staining ( Figure 4 F). Immunofluorescence results of tumor necrosis factor-α (TNF-α) showed that in both models, the single drug group and the single nanocoating group, as well as the SL loaded with DEX (SL+DEX) and the DL loaded with DEX (DL+DEX) groups, all showed different degrees of TNF-α inhibition. Among them, the DL+DEX group had the strongest inhibitory effect, which was comparable to the blank control group. Interestingly, it was observed that the components of the drug-loaded nanocoatings inhibited TNF-α in different corneal tissues to different degrees. DEX had a stronger inhibitory effect on the entire corneal layer, while the nanocoating had a more significant inhibitory effect on TNF-α in the corneal stromal layer. In addition, corneal proteins were extracted from the treated eyeballs, and the levels of inflammatory factors, including TNF-α, interleukin 1β (IL-1β), and interleukin 6 (IL-6) ( Figure 4 The results confirmed that the nanocoating itself had anti-inflammatory properties. The anti-inflammatory effect of the drug-loaded nanocoating was significantly enhanced compared with DEX or nanocoating alone, indicating that it has dual anti-inflammatory functions in vivo.
[0077] Application of ALJN in the treatment of corneal contusion
[0078] After verifying the long-term residence, sustained drug release, lubrication and anti-inflammatory ability of ALJN on the ocular surface in vitro and in vivo, the present invention then evaluated the therapeutic value of the drug delivery system in two animal models of ocular surface inflammatory diseases. Due to the exposure of the eye, external damage can easily cause structural and functional damage, making ocular trauma a common clinical disease and the main cause of monocular blindness. Inflammation is the body's initial response to injury and infection after eye injury, but severe inflammation can lead to further damage. Therefore, controlling ocular surface inflammation is a means to prevent further development of damage and a method to promote tissue repair. In view of the fact that ocular trauma can be divided into mechanical and non-mechanical according to the cause of injury, the present invention selects mouse corneal contusion and alkali burn models respectively to explore the potential of nano-coatings in treating corneal injuries.
[0079] First, to evaluate the therapeutic potential of ALJN in the treatment of mechanical corneal injury ( Figure 5 A). A corneal trephine and corneal scraper were used to establish a mouse corneal contusion model, causing mild corneal damage. After modeling, the surface of the mouse cornea was obviously rough and uneven under light. Topical eye drops were applied to the ocular surface of each group of mice once a day for 3 consecutive days. The corneal condition of the mice was monitored daily using a slit lamp ( Figure 5 BD). After 3 days of treatment, the corneal opacity in the DL+DEX group changed the least, and the surface reflected light very evenly, indicating that the corneal surface repair was effective. In contrast, the other groups showed varying degrees of corneal opacity and uneven light reflection. The corneal opacity score in the DL+DEX group (0.50±0.76 points) was significantly lower than that in the DEX group (2.50±1.20 points) and the control group (3.00±1.07 points) ( Figure 5 Although the inflammation caused by corneal contusion was relatively limited and the growth of corneal neovascularization was relatively slow, the area of corneal neovascularization in mice in the DL+DEX group (1.21±0.50mm 2 ) was significantly lower than that of the DL group (2.54±0.84mm 2 ), DEX group (3.12±1.11mm 2 ) and control group (3.75±0.39mm 2 )( Figure 5 In terms of corneal injury healing level, the DL+DEX group showed good efficacy (94.51±6.46%), which was significantly different from the DEX group (70.20±13.61%) and the control group (54.36±14.73%) ( Figure 5 G). These results indicate that drug-loaded DL plays an important role in promoting the healing of corneal injuries.
[0080] After 3 days of treatment, the corneal sections of mice in each group were subjected to H&E staining and Masson staining to observe the corneal morphology ( Figure 5H). Encouragingly, the corneas of the DL+DEX group showed near-normal stromal arrangement and regular epithelial layer, similar to those of the blank group. In the other groups, varying degrees of epithelial cell disorder or stromal edema were observed. Statistically, the corneal thickness of all coating groups was significantly different from that of the DEX and control groups ( Figure 5 I), indicating that the treatment not only suppressed the acute inflammatory response but also preserved the structural integrity of the cornea. Similar results were observed in the inhibition of corneal cell infiltration ( Figure 5 J), of which the DL+DEX group was significantly superior to the DEX and DL groups. The results demonstrated the combined effect of drugs and nanocoatings in the treatment of corneal injuries. The significant reduction in interstitial edema and epithelial disorder in the DL+DEX group indicated a more effective alleviation of the pathological process after corneal injury, which is essential for healing and prevention of long-term complications. The DL+DEX group had a significant inhibitory effect on the infiltration of corneal neutrophils. The results of the treatment of corneal contusions showed that in cases of mild corneal injuries, once-daily use of drug-loaded SL or DL nanocoated eye drops had similar effects on inhibiting acute corneal inflammation. It is worth noting that DL+DEX has additional lubricating ability, which can improve ocular surface comfort.
[0081] Application of ALJN in the treatment of corneal alkali burns
[0082] Next, the present invention further constructed a more serious and urgent corneal injury model, namely the corneal alkali burn model, to evaluate the therapeutic potential of ALJN. Chemical injury to the ocular surface is a common ocular emergency, with an estimated incidence of 5.1-50 cases per 100,000 people per year. Ocular alkali burns account for 11.5% to 22.1% of all ocular injuries and are considered to be one of the most serious types of chemical injuries to the eye. However, current treatments for alkali burns have some limitations, such as frequent administration, low bioavailability, and unsatisfactory therapeutic effects. Accordingly, Figure 6 As shown in A, mice were treated with sodium hydroxide to construct a corneal alkali burn model. The cornea of healthy mice is transparent, and there is no defect in sodium fluorescein staining. The difference is that increased opacity was observed at the injury site of the model mice, showing white color and large-area staining. From the day of modeling, each group of mice was instilled with DEX, DL, SL+DEX, and DL+DEX, respectively, once a day for 5 consecutive days. The control group (administered with an equal amount of PBS) and the non-modeling blank group were compared to observe the therapeutic effect. During the treatment, a slit lamp was used to monitor the corneal opacity, corneal neovascularization area and corneal damage area of the mice ( Figure 6 BD). On the 5th day of treatment, corneal opacity in the DL+DEX group was significantly reduced, and the pupil and iris were clearly visible. In the SL+DEX group, the pupil and iris were less obvious. However, the changes between the DEX group and the control group were negligible, and the pupils were almost indistinguishable. Corneal opacity scores were performed for each mouse ( Figure 6The results of the E) showed that the improvement of the DEX+DL group (2.29±1.11 points) was significantly better than that of the control group (3.86±0.38 points) and the DEX group (3.57±0.53 points), indicating that the combined use of DL and DEX is effective in reducing corneal opacity. Compared with the DEX group and the control group, the inhibitory effect of the DL+DEX group on corneal neovascularization was significantly improved ( Figure 6 The results showed that the corneal neovascularization of the control group expanded to half of the cornea (5.54±0.77mm 2 The corneal neovascularization in the DEX group expanded by about 1 / 3 (4.45±0.56mm 2 ), while the corneal neovascularization in the DL+DEX group was almost not expanded (1.54±0.67mm 2 The degree of wound healing was evaluated based on the ratio of the sodium fluorescein staining area to the area on the day of modeling ( Figure 6 The results showed that the degree of wound healing in the DL+DEX group (76.32±13.47%) was significantly higher than that in the control group (31.25±22.15%) and the DEX group (35.88±15.00%). However, there was no significant difference between the DEX group and the control group.
[0083] In addition to the destruction of epithelial integrity visible under slit lamp, corneal edema and infiltration of inflammatory cells and factors are also common histopathological manifestations of corneal injury. Therefore, the mouse cornea was histologically examined after hematoxylin and eosin (H&E) and Masson staining ( Figure 6 H). The corneal sections of the DL+DEX group showed that the corneal epithelial and stromal layers were neatly arranged and clear, similar to the blank group. However, compared with the control group, the corneal stroma in the DEX group was significantly thickened, edematous, infiltrated with inflammatory cells, and the arrangement of epithelial cells was relatively disordered. Compared with the DEX and control groups, the DL+DEX group had statistically significant differences in inhibiting corneal edema and inflammatory cell infiltration, indicating that the efficacy in these aspects was better ( Figure 6 I, J). It has been reported that neutrophils and their extracts can slow down the healing of the corneal epithelium in mice and can also secrete inflammatory factors that further damage the cornea. Therefore, we further performed immunostaining on corneal sections and found that DL+DEX can effectively inhibit the infiltration of neutrophils ( Figure 6 The above results indicate that the therapeutic effect of DL is better than that of SL drug-loaded nanocoating in the corneal alkali burn model with more severe inflammation.
[0084] In summary, the present invention provides a nano-coating eye drops, wherein the nano-coating is a polyphenol compound TA and a metal ion Fe 3+ PMPC and metal ion Fe 3+It is formed by the complexation between the phosphorylcholine-dependent groups. After continuous local administration in the form of eye drops, the two layers of nanocoating spontaneously assemble on the surface of the eye to form a double-layer nanocoating structure. The drug-loaded inner layer can remain on the surface of the eye for a long time and provide sustained release of the drug. The lubricating outer layer provides interface lubrication to ensure comfort and prevent adhesion between the nanocoating and the eyelids. It can inhibit the formation of corneal neovascularization, accelerate the repair of corneal damage, and inhibit the infiltration of inflammatory cells and factors.
[0085] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing nano-coating eye drops, characterized in that: At least the following steps are included: Step 1: Mix tannic acid solution with Fe 3+ The metal ion solution is mixed evenly, and the catechol group of the tannic acid is mixed with the Fe 3+ The metal ions are coordinated and complexed, and after the first step of dripping, an adhesion inner layer is formed; the drug dexamethasone is dripped into the adhesion inner layer, and the mixture is blown and mixed to obtain the adhesion inner layer loaded with the drug; Step 2, dripping the poly 2-methacryloyloxyethyl phosphorylcholine solution in the second step, the phosphorylcholine groups in the poly 2-methacryloyloxyethyl phosphorylcholine solution are attached to the Fe 3+ The metal ions undergo coordination and complexation to form a lubricating outer layer; The drug-loaded adhesive inner layer and the lubricating outer layer constitute nano-coating eye drops.
2. The preparation method according to claim 1, characterized in that In step 1, the tannic acid solution is, by molar ratio, Fe 3+ Metal ion solution = 1:
3.
3. The preparation method according to claim 1, characterized in that: The surface pores of the adhesive inner layer are larger than the surface pores of the lubricating outer layer.
4. The preparation method according to claim 1, characterized in that: The depth of the surface pores of the inner adhesive layer is greater than the depth of the surface pores of the outer lubricating layer.
5. The preparation method according to claim 1, characterized in that: In the drug-loaded adhesive inner layer, the drug concentration was 1 mg / mL.
6. A nano-coated eye drop, characterized in that: The nano-coating eye drops are prepared by the preparation method described in any one of claims 1 to 5.
7. The nano-coated eye drops according to claim 6, characterized in that: The nano-coated eye drops comprise an adhesive inner layer and a lubricating outer layer, wherein the adhesive inner layer is composed of tannic acid and Fe 3+ The lubricating outer layer is formed by the coordination complexation of metal ions, and the phosphorylcholine groups in the poly 2-methacryloyloxyethyl phosphorylcholine solution and Fe 3+ Coordination complex formation of metal ions.
8. An application of nano-coated eye drops, characterized in that: The nano-coating eye drops are used for preparing medicine for treating corneal contusion.
9. The use according to claim 8, characterized in that The nano-coating eye drops are used for preparing medicine for treating corneal alkali burns.